Yellow-Orange MEH-PPV Organic Light Emitting Diode (OLED) - Nurjuliana, Juhari (Malaysian Invention and Design Society (MINDS), 2010)
Nurjuliana and her team won bronze for Yellow-Orange MEH-PPV Organic Light Emitting Diode (OLED). ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.